Response inhibition is linked to emotional devaluation: behavioural and electrophysiological evidence - Kiss, Monika; Raymond, Jane E.; Westoby, Nikki; Nobre, Anna C.; Eimer, Martin (Frontiers in Human Neuroscience, 2008)
To study links between the inhibition of motor responses and emotional evaluation, we combined electrophysiological measures of prefrontal response inhibition with behavioural measures of affective evaluation. Participants first performed a Go-Nogo task in response to Asian and Caucasian faces (with race determining their Go or Nogo status), followed by a trustworthiness rating for each face. Faces previously seen as Nogo stimuli were rated as less trustworthy than previous Go stimuli. To study links between the efficiency of response inhibition in the Go-Nogo task and subsequent emotional evaluations, the Nogo N2 component was quantified separately for faces that were later judged to be high versus low in trustworthiness. Nogo N2 amplitudes were larger in response to low-rated as compared to high-rated faces, demonstrating that trial-by-trial variations in the efficiency of response inhibition triggered by Nogo faces, as measured by the Nogo N2 component, co-vary with their subsequent affective evaluation. These results suggest close links between inhibitory processes in top-down motor control and emotional responses.